Cfd simulation study on the effect of water velocity towards oil leakage from submarine pipelines - Amarasingam, Selvarajah (2014)
This paper presents Computational fluid dynamic (CFD) studies on water velocity effect towards the time taken for migration of oil droplets to reach free surface. Computational Fluid Dynamic (CFD) simulations with FLUENT software 6.3.26 were simulated to detect the leakage process of oil spill from submarine pipeline to free surface. GAMBIT 2.4.6 mesh-generator is employed to perform all geometry generation and meshing. The velocity inlet of water (vs.) was varied whereas density of oil (kerosene liquid) was constant at 780kg/m3 .A computational rectangular domain with length of 20m and height of 15m was simulated in Gambit 2.4.6. The mesh was generated and exported to Fluent. In the Fluent 6.3.26, the time taken for the oil droplets to reach free surface was observed by varying water inlet velocity; vw1=0.02m/s, vw2=0.04m/s,vw3=0.08m/s respectively. Kerosene droplets reached free surface faster as the velocity of water inlet increased. Results were observed at 1000 number of time steps (iterations) with a step size of 0.1seconds. The leak size was shown to be 0.1meter, which was fixed at the beginning of the simulation conditions. Justifications were shown where oil droplets released from a greater leak width are easier to collision and have greater chance of gathering into large droplets, (Zhu et al., 2013). This is because at a larger face of leakage, the shear stresses increases, causing a larger displacement in oil migration. From the study, the dimensionless longest horizontal distance the kerosene droplets migrate when they reach the sea surface are analysed and the fitting formulas are obtained. With this, the maximum horizontal migration distance of oil at certain time is predicted, and a forecasting model is proposed in order to place the oil containment boom. This helps to detect the leakage more accurately and reduces cost of handling